Análisis multitemporal de la temperatura de la superficie terrestre (LTS) en el Área de Páramos Cruz Verde – Sumapaz (2025)
Land Surface Temperature (LST) is a variable that allows for the identification of the climatic conditions of a region. The “Complejo de Paramos Cruz Verde – Sumapaz” (CPCVS), being considered the largest in the world, becomes a zone of great importance for both Colombia and the world. This study is a multitemporal analysis to verify the variation of LST over two decades (2000 – 2020), using the Moderate Resolution Imaging Spectroradiometer (MODIS), specifically Terra (MOD11A2). The analyzed bands are "LST_Day_1km" and "LST_Night_1km." For the comparison of the two study years, the rainy and dry seasons were established for both daytime and nighttime.